Dengue Surveillance in the French Armed Forces: A Dengue Sentinel Surveillance System in Countries Without Efficient Local Epidemiological Surveillance. Issue 4 (12th December 2012) - de Laval, Franck; Dia, Aissata; Plumet, Sébastien; Decam, Christophe; Leparc Goffart, Isabelle; Deparis, Xavier
Abstract Surveillance of travel‐acquired dengue could improve dengue risk estimation in countries without ability. Surveillance in the French army in 2010 to 2011 highlighted 330 dengue cases, mainly in French West Indies and Guiana: DENV‐1 circulated in Guadeloupe, Martinique, French Guiana, New Caledonia, Djibouti; DENV‐3 in Mayotte and Djibouti; and DENV‐4 in French Guiana.